2019
DOI: 10.3389/fpsyt.2019.00698
|View full text |Cite
|
Sign up to set email alerts
|

Low Self-Esteem and Its Association With Anxiety, Depression, and Suicidal Ideation in Vietnamese Secondary School Students: A Cross-Sectional Study

Abstract: Background: There is a correlation between self-esteem in adolescents and risks and protective factors for their health and welfare. The study was conducted to determine the prevalence of low self-esteem and sociodemographic features related to anxiety, depression, educational stress, and suicidal ideation in secondary school students in Vietnam.Methods: A cross-sectional design was employed for this study with participation of 1,149 students in Cantho City in Vietnam. A structured questionnaire was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
146
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(175 citation statements)
references
References 36 publications
18
146
0
11
Order By: Relevance
“…Literature has shown that high levels of anxiety reduce learning efficiency by decreasing attention, concentration and retention, with the consequent deterioration in school performance (Van Ameringen et al, 2003;Visu-Petra et al, 2014;Respondek et al, 2017). For this reason, it is very important to treat anxiety that comes from identifying symptoms because decreased school performance negatively affects marks as well as adolescent students' self-esteem (Nguyen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that high levels of anxiety reduce learning efficiency by decreasing attention, concentration and retention, with the consequent deterioration in school performance (Van Ameringen et al, 2003;Visu-Petra et al, 2014;Respondek et al, 2017). For this reason, it is very important to treat anxiety that comes from identifying symptoms because decreased school performance negatively affects marks as well as adolescent students' self-esteem (Nguyen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have been accumulating evidence that some stressful conditions may increase the risk for suicidal ideation and attempts [ 21 23 ], such as an overloading persisting situation, constant stress, and negative life experiences or incidents, leading to mental health disorders and suicidal ideation [ 23 ]. Low self-esteem was also linked to increased suicidal tendencies and tentative [ 24 26 ]. A constant negative view of oneself may include seeing oneself as worthless, the future as hopeless, and life as not worth living [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diathesis-stress model could help explain why Zhongyong thinking could be related to college student’s emotion. Based on the diathesis-stress model, individuals with some personality traits, such as poor self-esteem ( Nguyen et al, 2019 ), low self-directedness and cooperativeness ( Lim et al, 2018 ), low agreeableness ( Roman et al, 2019 ), and high perfectionism ( Bußenius and Harendza, 2019 ), may predispose them to develop more depression and anxiety symptoms. Results from two cross-sectional studies demonstrated that Chinese adults with high level of Zhongyong thinking style had few depressive and anxiety symptoms ( Zhan et al, 2013 ; Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%